Law and religion in South Africa: An African traditional perspective - Mndende, Nokuzola (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The discussion on the relationship between the law and religion in the South African context by somebody whose background and point of reference are based on the indigenous customary law of the land needs a special and honest approach. For the right approach, it is important that one has to be first honest to the inner self, to the religious community s/ he serves and then to the nation as a whole. I find it very difficult to compromise my inner self because I am expected to be politically correct even if I find flaws in the law of the land or I find some aspects of deliberate negligence in the implementation of the policies that are supposed to liberate all. This paper will therefore be straight to the point and will not be subjected to any blind loyalty either to the Constitution as the supreme law of the country or to the government programs and their attitude towards indigenous religion. It must be noted that there is a wide gap between what is said in the Constitution and the implementation of the theories documented. The Constitution of the country as the supreme law of the land is, on some very important issues too superficial and accommodating at the expense of the previously and in-fact still disadvantaged religious communities.